Living liveable? RESIDE's evaluation of the "Liveable Neighborhoods" planning policy on the health supportive behaviors and wellbeing of residents in Perth, Western Australia. (April 2020) - Hooper, Paula; Foster, Sarah; Bull, Fiona; Knuiman, Matthew; Christian, Hayley; Timperio, Anna; Wood, Lisa; Trapp, Gina; Boruff, Bryan; Francis, Jacinta; Strange, Cecily; Badland, Hannah; et al.
Abstract: Background: The RESIDential Environments (RESIDE) project is a unique longitudinal natural experiment designed to evaluate the health impacts of the "Liveable Neighbourhoods" planning policy, which was introduced by the Western Australian government to create more walkable suburbs. Objectives: To summarize the RESIDE evidence of the impact of the planning policy on a range of health-supportive behaviours and wellbeing outcomes and to assess the consistency and direction of the estimates of associations. Methods: An audit of 26 RESIDE research papers (from 2003 to 2012) identified the number of positive associations (statistically significant and consistent with policy expectations), negative associations (statistically significant and inconsistent with policy expectations), and null findings from multiple-exposure models between objective and perceived measures of 20 policy design requirements and 13 health-supportive behaviors and wellbeing outcomes. Results: In total 332 eligible estimates of associations ( n = 257 objective measures and n = 75 perceived measures) were identified. Positively significant findings were detected for: 57% of walking estimates with objectively measured policy design features (negative = 3%; null = 40%) ( n = 115) and 54% perceived measures (negative = 0%; null = 33%) ( n = 27); 42% of sense of community estimates with objectively measured of policy design features (negative = 8%; null = 50%) ( n = 12) and 61% perceived measures (negative = 8%; null = 31%) ( n = 13); 39% of safety or crime-related estimates with objectively measured of policy design features (negative = 22%; null = 39%) ( n = 28) and 100% perceived measures ( n = 7). All (n = 4) estimates for mental health outcomes with objectively measured policy-related design features were positively significant. Conclusions: The synthesis of findings suggests that new suburban communities built in accordance with the "Liveable Neighbourhoods" policy have the potential to encourage health supportive behaviors and wellbeing outcomes including transport and recreation walking, and to create neighborhoods with a stronger sense of community where residents may feel safer. Highlights: The RESIDE study is a longitudinal natural experiment evaluating a new planning policy to create more walkable suburbs. A process evaluation quantified how much of the policy had been implemented on-the-ground. This review included 332 estimated associations from multiple-exposure predictor models extracted from 26 RESIDE papers. It summarized the consistency, strength and direction of estimates of associations against the policy expectations. New communities built to the policy principles may encourage walking and a sense of community where residents feel safer.